Answer:
The answer to your question is:
Step-by-step explanation:
![\frac{x^{2}-16 }{2x + 4} \frac{x^{3}-2x^{2} + x }{x^{2}+ 3x - 4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D-16%20%7D%7B2x%20%2B%204%7D%20%5Cfrac%7Bx%5E%7B3%7D-2x%5E%7B2%7D%20%2B%20x%20%7D%7Bx%5E%7B2%7D%2B%203x%20-%204%7D)
Factorize ![\frac{(x+4)(x-4)}{2(x+2)} \frac{x(x^{2}-2x + 1) }{(x+4)(x-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%2B4%29%28x-4%29%7D%7B2%28x%2B2%29%7D%20%20%5Cfrac%7Bx%28x%5E%7B2%7D-2x%20%2B%201%29%20%7D%7B%28x%2B4%29%28x-1%29%7D)
Factorize ![\frac{(x+4)(x-4)}{2(x+2)} \frac{x(x-1)^{2} }{(x+4)(x-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%2B4%29%28x-4%29%7D%7B2%28x%2B2%29%7D%20%5Cfrac%7Bx%28x-1%29%5E%7B2%7D%20%7D%7B%28x%2B4%29%28x-1%29%7D)
Simplify ![\frac{x(x-4)}{2(x+2)}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%28x-4%29%7D%7B2%28x%2B2%29%7D)
The answer is 6. The first two absolute values cancel each other and subtracting a negative is adding.
<span>A) 4x − 2y − z = −5
B) x − 3y + 2z = 3
C) 3x + y − 2z = −5
Looking at ALL 4 solutions, x =0 in all of them.
So, let's say x = 0, eliminate the "x's" and just keep equations B and C
</span>
<span>B) -3y + 2z = 3
C) y − 2z = −5
</span>Add B) and C)
-2 y = -2
y = 1
<span>1 − 2z = −5
</span>-2z = -6
z = 3
and x = 0
Answer:
remember the chain rule:
h(x) = f(g(x))
h'(x) = f'(g(x))*g'(x)
or:
dh/dx = (df/dg)*(dg/dx)
we know that:
z = 4*e^x*ln(y)
where:
y = u*sin(v)
x = ln(u*cos(v))
We want to find:
dz/du
because y and x are functions of u, we can write this as:
dz/du = (dz/dx)*(dx/du) + (dz/dy)*(dy/du)
where:
(dz/dx) = 4*e^x*ln(y)
(dz/dy) = 4*e^x*(1/y)
(dx/du) = 1/(u*cos(v))*cos(v) = 1/u
(dy/du) = sin(v)
Replacing all of these we get:
dz/du = (4*e^x*ln(y))*( 1/u) + 4*e^x*(1/y)*sin(v)
= 4*e^x*( ln(y)/u + sin(v)/y)
replacing x and y we get:
dz/du = 4*e^(ln (u cos v))*( ln(u sin v)/u + sin(v)/(u*sin(v))
dz/du = 4*(u*cos(v))*(ln(u*sin(v))/u + 1/u)
Now let's do the same for dz/dv
dz/dv = (dz/dx)*(dx/dv) + (dz/dy)*(dy/dv)
where:
(dz/dx) = 4*e^x*ln(y)
(dz/dy) = 4*e^x*(1/y)
(dx/dv) = 1/(cos(v))*-sin(v) = -tan(v)
(dy/dv) = u*cos(v)
then:
dz/dv = 4*e^x*[ -ln(y)*tan(v) + u*cos(v)/y]
replacing the values of x and y we get:
dz/dv = 4*e^(ln(u*cos(v)))*[ -ln(u*sin(v))*tan(v) + u*cos(v)/(u*sin(v))]
dz/dv = 4*(u*cos(v))*[ -ln(u*sin(v))*tan(v) + 1/tan(v)]